Iliac artery aneurysm: a life-threatening cause of abdominal pain - Ayala Garcia, Ricardo Jonathan (2023)
Life-Threatening abdominal pain is a common condition in emergency departments and it is associated with high morbidity and mortality, if not promptly and accurately diagnosed and treated. A man with symptoms of renal colic presented to the emergency room with severe abdominal pain and clinical deterioration. After a CT scan, an aneurysmatic image was found in the left primitive iliac artery. The patient was taken to an operating room for surgical repair but died. Life-Threatening abdominal pain requires a comprehensive diagnostic approach and individualized treatment to prevent serious complications. The complicated iliac artery aneurysm is a potentially serious cause of abdominal pain in elderly male smokers with a history of hypertension and atherosclerosis.